2020
DOI: 10.1007/s40940-020-00132-8
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for structural glass engineering applications — overview, case studies and future potentials

Abstract: ’Big data’ and the use of ’Artificial Intelligence’ (AI) is currently advancing due to the increasing and even cheaper data collection and processing capabilities. Social and economical change is predicted by numerous company leaders, politicians and researchers. Machine and Deep Learning (ML/DL) are sub-types of AI, which are gaining high interest within the community of data scientists and engineers worldwide. Obviously, this global trend does not stop at structural glass engineering, so that, the first part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 137 publications
0
20
0
11
Order By: Relevance
“…The AI model relies on the input of grey-value images after pummeling the laminated glass. This example showed that an AI-approach can successfully be trained to standardize, automate and objectify human-based classification of pummel images into the Pummel categories during production control along with a statistically sound quantification of uncertainties of this process (further details can also be found in [5]). Since the training of the CNN within this example was based on a small amount of publicly available data, more theoretical justification for a potential Pummel class lumping along with a quantification of the improvement of the performance and robustness of the CNN and further investigations on alternative architectures or even alternative approaches such as clustering [35] has to build upon future studies with an increasing amount of ground-truth Pummel images.…”
Section: Ai For Quality Assurance and Inspection Of Glass Productsmentioning
confidence: 99%
See 2 more Smart Citations
“…The AI model relies on the input of grey-value images after pummeling the laminated glass. This example showed that an AI-approach can successfully be trained to standardize, automate and objectify human-based classification of pummel images into the Pummel categories during production control along with a statistically sound quantification of uncertainties of this process (further details can also be found in [5]). Since the training of the CNN within this example was based on a small amount of publicly available data, more theoretical justification for a potential Pummel class lumping along with a quantification of the improvement of the performance and robustness of the CNN and further investigations on alternative architectures or even alternative approaches such as clustering [35] has to build upon future studies with an increasing amount of ground-truth Pummel images.…”
Section: Ai For Quality Assurance and Inspection Of Glass Productsmentioning
confidence: 99%
“…This system uses adaptive elements within the facade (windows, shading elements, air conditioning) and sensors (humidity, wind speed, temperature, user feedback via smart watches) together with an AI controlling unit to process all data and learn over time the individual preferences of the occupants. Further details and explanations can be found in [5].…”
Section: Potential 3: "Intelligent Home/ Office" -User-centered Buildings By Aimentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that a combination of AI algorithms can boost the prediction efficiency [22]. Overall, the fields of statistics, numerics, and optimization are critical aspects that facilitate understanding the data, describing the properties of a dataset, finding relationships and patterns in the data, as well as choosing and implementing the suitable AI model.…”
Section: Evolutionary Computation Techniques For Predicting Consistency Limit: Genetic Programming and Artificial Neuralmentioning
confidence: 99%
“…Zu allen drei genannten Punkten existieren erste Publikationen zur Anwendung von KI oder einer Unterform. Eine glasbauzentrierte Diskussion von Potenzialen zum Einsatz von KI und eine Sammlung spezifischerer Details zu den drei genannten Bereichen ist in zu finden. Es ist allerdings insgesamt festzustellen, dass die heute existierenden Ansätze noch weitere Jahre der Forschung und Zusammenarbeit zwischen den verschiedenen Disziplinen und insbesondere der Praxis und Wissenschaft benötigen, um die benötigte Zuverlässigkeit und Qualität für einen gewinnbringenden Einsatz im Planer‐ und Baualltag zu erreichen.…”
Section: Potenziale Und Zukunftstrends Von Künstlicher Intelligenz Imunclassified